LEGAL ANALYSIS OF THE SUPREME COURT DECISION NUMBER 2319 K/PID, SUS/2024 CONCERNING FIDUCIARY GUARANTEES IN MUAMALAH FIQH - Mumtazul Fikri; Shabarullah (JURISTA: Jurnal Hukum dan Keadilan, 2025)
This research analyses Supreme Court Decision No. 2319 K/Pid.Sus/2024, which imposes a penalty for breach of the fiduciary guarantee agreement in the case of unauthorised transfer of collateral objects. This research aims to examine aspects of positive law and Islamic law related to the practice of fiduciary guarantees in Indonesia and assess the suitability of the verdict with the principles of justice in Islam. Using a descriptive-normative qualitative method and a content analysis approach, this study found that the Supreme Court not only upheld positive legal norms stipulated in Law No. 42/1999, but also considered moral and Sharia principles that emphasise trustworthiness and the prohibition of khiyanah. The decision provides legal certainty for financial institutions and protection for creditors and debtors, and on the other hand, shows the importance of harmonisation between national law and the principles of Islamic law in the Indonesian legal system.